Life Cycle Impact Assessment (LCIA) using TRACI methodology: An analysis of potential impact on potable water production - Sharaai, Amir Hamzah; Mahmood, Noor Zalina; Sulaiman, Abdul Halim (American-Eurasian Network for Scientific Information, Jordan, 2010)
Life cycle assessment (LCA) is a method to analyse a particular product or service. It begins with the process of extraction until the product is exhausted by 'cradle-to-grave' analysis. The LCA includes establishment of an inventory, that is all types of emissions and also waste products. After that, this inventory would be translated or transformed to show the impact on environment in the life cycle impact assessment (LCIA). Two LCIA methods has been accepted such as Midpoint and Endpoint approach. TRACI is one method that uses Midpoint approach. From the analysis on the two stages of potable water production, that is between construction stage and production stage, production stage contributes a higher impact in comparison to the construction stage. At the production stage, the weakness was due to the usage of PAC, lime and electricity. However, at the construction stage, the process of producing steel seems to be the main source of impact such as HH cancer and HH noncancer. The process of producing PAC liberates Nitrogen oxides and Sulfur oxides which contributes to five types of impacts such as acidification, HH criteria air - point, HH criteria air - mobile, euthrophication and smog. In lime production, four impacts are HH cancer ground - surface, HH cancer root - zone, HH noncancer ground - surface and HH noncancer root -zone) results from the emissions during the waste treatment (drilling waste to land farming) such as Arsenic and Aluminum. Whereas in the production of electricity, four very high impacts give rise to global warming, HH cancer, HH noncancer dan ecotoxicity. Even though the impact from construction stage is very low in comparison to the production stage, a few problems have been detected during the process of producing building materials. Among those materials, the production of steel produces the highest impact to the environment. Â© 2010, INSInet Publication.